2016
DOI: 10.7439/ijbar.v7i5.3253
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Allergic Broncho Pulmonary Aspergillosis in patients with Asthma attending allergy clinic in a North West Indian Tertiary Care Institute

Abstract: Context: Allergic Broncho Pulmonary Aspergillosis (ABPA) is an allergic disorder. Aspergillus fumigatus is the most common pathogen responsible for occurrence of ABPA. There can be serious consequences of ABPA including worsening of symptoms of asthma and more sinister complications like extensive fibrosis and bronchiectasis. Aims: To find out the prevalence of ABPA among asthma patients and association of former with factors like age, sex, occupation, family history of bronchial asthma, socioeconomic status a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…Our positivity rate of SPT Af was lower than reported rate by Hendrick et al (16.0%), 24 Eaton et al (18.4%), 25 Maurya et al (28.5%) 16 and Agarwal et al 17 (39.5%) studies. However, in our study we observed a higher prevalence of SPT Af positivity than those of reported by Ma et al 26 (5.5%) and Mathur and Mathur 27 (9.0%) studies. Several factors may affect the positivity ratio of SPT Af prevalence, including the use of various fungal allergens or exclusive use of A fumigatus antigens, using different diagnostic criteria for interpreting of a positive skin test and difference in the type of skin test (SPT or intradermal skin test) 10 .…”
Section: Discussioncontrasting
confidence: 79%
“…Our positivity rate of SPT Af was lower than reported rate by Hendrick et al (16.0%), 24 Eaton et al (18.4%), 25 Maurya et al (28.5%) 16 and Agarwal et al 17 (39.5%) studies. However, in our study we observed a higher prevalence of SPT Af positivity than those of reported by Ma et al 26 (5.5%) and Mathur and Mathur 27 (9.0%) studies. Several factors may affect the positivity ratio of SPT Af prevalence, including the use of various fungal allergens or exclusive use of A fumigatus antigens, using different diagnostic criteria for interpreting of a positive skin test and difference in the type of skin test (SPT or intradermal skin test) 10 .…”
Section: Discussioncontrasting
confidence: 79%
“…In a study of 57 patients with severe acute asthma admitted to an intensive care unit, the prevalence of ABPA was found to be 39 per cent (compared to 21% in the outpatient asthma group) 20 . The prevalence of ABPA complicating asthma reported in the last decade is summarized in Table I 21 22 23 24 25 26 27 28 29 30 31 32 . The data suggest a high prevalence of AS and ABPA in special clinics ( Table I ) and a higher prevalence in India compared to other countries.…”
Section: Epidemiology Of Abpamentioning
confidence: 99%